Antioxidants Based on Gossypol and Epichlorohydrin and Their Application Polyethylene (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In this paper, the study of a new antioxidant based on gossypol with epichlorohydrin (ECH) was carried out in two ways: in the presence of 1% phosphoric acid and 0.5% alkali solution in a molar ratio of gossypol: alkali=1:2. Obtained in the presence of phosphoric acid, has the following characteristics: it is a homogeneous brown powder, average molecular weight 2300-3500, non-volatile, main component content 99.6% and in an alkaline environment, has the following characteristics: uniform brown powder, average molecular weight 2500-3800, non-volatile, main component content 99.7%. The technological regime of the optimal conditions for the synthesis of gossypol with epichlorohydrin is carried out at a molar ratio of 1:1 in the temperature range of 313–353 K in an alcohol solution. The structure of this compound was confirmed by IR, 1H NMR, spectral and elemental analysis. For comparison, IR spectra of gossypol and its oligomeric derivatives GECH were taken. This obtained oligomer was applied to polyethylene as an antioxidant and improved its mechanical and thermal properties.